Perception of problem-based learning and development of abilities in students of a Faculty of Stomatology - Lamas Lara, Víctor Fernando (2017)
Objective: To determine the relationship between the students' perception of the use of problem-based learning based on problems and the development of abilities in the Faculty of Stomatology of the Inca Garcilaso de la Vega University (UIGV). Materials and method: Descriptive, cross-sectional and correlational study. The population was students of the fifth cycle the Faculty of Stomatology of the UIGV of 2015-I, that were taking removable partial prosthesis and who met the inclusion (enrolled in the subject of Removable Partial Prosthesis of the year 2015-I, accessibility, availability and acceptance of participation in the study). We worked with 49 students. The instrument used: An evaluation questionnaire. The tenor of the questions inquires about the perception that the student develops on the methodology of learning based on problems and the development of abilities that considers to have developed. Results: No correlation was found between the dimension conditions on the use of the didactic model of learning based on problems with the development of conceptual, procedural and attitudinal abilities by means of the Spearman correlation test. The instrumental dimension and the development of conceptual, procedural and attitudinal abilities by the Spearman test had a moderate direct correlation in all of them (p < 0.001) with Spearman rho index values of 0.524, 0.481 and 0.503 respectively. Conclusions: The students' perception of problem based learning strategy correlates positively with the development of abilities.